ANALISIS PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN SESUAI UU NO. 36 TAHUN 2008 TERHADAP PRAKTIK EARNINGS MANAGEMENT SEBAGAI MOTIVASI PENGHEMATAN PPh BADAN - Endin Dwi Woro Widyawanti; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aims to examine the differences of firm’s discretionary accrual whether before and after corporate income tax rate changes according to “UU No. 36 Tahun 2008”, from 30% to 28% in year 2009, and 25% in year 2010 with 5% added incentives for the firms which “go public” and deposited stock as minimal 40%. Over that, this study also aims to analyze how practical of earnings management by firms before and after corporate income tax rate changes for saving on taxes. The research samples were 64 manufacturing sector companies which listed in Indonesia Stock Exchange in periods 2008-2010.The analysis method in this study uses test different T-test and multiple regression analysis. Test different T-test uses paired sample T-test to examine whether there’s significant differences of discretionary accrual at before and after corporate income tax rate decreases. While paired sample T-test is used to examine how practical of earnings management by profit firms in responding to these corporate income tax rate decreases with discretionary accrual approach.The results of this research showed that in years 2009 and 2010 is proved that sample firms do the practical of earnings management by delaying the reporting income in year 2009 and bestow that income to year 2010 for getting more save on taxes. Over that, the practical of earnings management by firms in responding corporate income tax rate decreases were influenced by tax incentives, there was tax planning, and non tax incentives, there were earnings pressure and earnings bath.